PROMOSI KACANG PKUL HH SEBAGAI CINDERAMATA KHAS KABUPATEN ROKAN HILIR - Putri, Ayu Aulia; Yusrizal, Firdaus (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study aims to examine the promotional strategy implemented by Toko Kacang Pukul HH as a typical souvenir of Rokan Hilir Regency, and to analyze consumer perceptions of the effectiveness of the promotion. This product has significant cultural and economic value, but the promotional strategy has not been fully evaluated based on the consumer's perspective. The research method used is a mixed method, with a qualitative approach through observation and interviews, and a quantitative approach through distributing questionnaires to 153 respondents using the accidental sampling technique. Data analysis was carried out descriptively with a frequency approach. The results showed that promotion was carried out through advertising, personal selling, and public relations. Consumers generally responded positively to the appearance of advertisements and staff services, but the promotion was considered inconsistent and had not reached the market optimally. This study contributes to the development of local product promotion strategies based on consumer perceptions to support the competitiveness of the regional tourism sector. Keywords: promotional strategy, kacang pukul, souvenir, consumer perception, tourism, Rokan Hilir